Anisotropy of the critical curremt due to twin planes and vortex melting in YBa₂Cu₃O₇₋x single crystals - Obolenskii, M.A.; Bondarenko, A.V.; Shklovskij, V.A.; Revyakina, M.G. (Физика низких температур, 1996)
We have measured the anisotropy of the critical current due to vortex pinning by twin boundaries and compared it with calculated values. We have also investigated current-voltage characteristics, which allowed us to obtain the temperature dependences of the depinning critical current and flux flow resistance. The results are discussed within the framework of the vortex melting transition and transition from unpinned to partially pinned state of the vortex-fluid phase.